2020
DOI: 10.3892/or.2020.7787
|View full text |Cite
|
Sign up to set email alerts
|

Effects and mechanisms of fatty acid metabolism‑mediated glycolysis regulated by betulinic acid‑loaded nanoliposomes in colorectal cancer

Abstract: Although previous studies have demonstrated that triterpenoids, such as betulinic acid (BA), can inhibit tumor cell growth, their potential targets in colorectal cancer (CRC) metabolism have not been systematically investigated. In the present study, BA-loaded nanoliposomes (BA-NLs) were prepared, and their effects on CRC cell lines were evaluated. The aim of the present study was to determine the anticancer mechanisms of action of BA-NLs in fatty acid metabolism-mediated glycolysis, and investigate the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…In the present study, we analyzed the BA effects on human melanoma cells using the Seahorse XFe24 extracellular flux analyzer and showed the dose-dependent inhibition of both mitochondrial respiration and glycolysis. Our data are in line with a recent study demonstrating that citrate synthase activity, glycolysis rate and carbon flux through the TCA cycle were inhibited in BA-loaded nanoliposomes-treated colorectal cancer cells; the results were confirmed by the glycolysis stress test in which ECAR values revealed that both the basal glycolysis and the maximum glycolytic capacity were reduced by BA-loaded nanoliposomes [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we analyzed the BA effects on human melanoma cells using the Seahorse XFe24 extracellular flux analyzer and showed the dose-dependent inhibition of both mitochondrial respiration and glycolysis. Our data are in line with a recent study demonstrating that citrate synthase activity, glycolysis rate and carbon flux through the TCA cycle were inhibited in BA-loaded nanoliposomes-treated colorectal cancer cells; the results were confirmed by the glycolysis stress test in which ECAR values revealed that both the basal glycolysis and the maximum glycolytic capacity were reduced by BA-loaded nanoliposomes [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, the role of PLCB4 in OXA resistance requires further studies for verification. [38][39][40][41][42][43] STC2 is implicated in glucose homeostasis, phosphorus metabolism, and various malignancies. Studies have consistently reported higher STC2 levels in CRC tissues compared to normal tissues, with correlations observed with tumor size, histological grade, lymph node metastasis, lymphatic invasion, and tumor depth.…”
Section: Discussionmentioning
confidence: 99%
“…In CRC, downregulation of PLCB4 is associated with oxaliplatin (OXA) resistance. However, the role of PLCB4 in OXA resistance requires further studies for verification 38–43 …”
Section: Discussionmentioning
confidence: 99%
“…Parthenolide derivatives reduce PKM2 expression in CRC cells, inhibit the PKM2/STAT3 signaling pathway, and PKM2 dimerization in nuclear translocation, inhibiting CRC tumor growth ( 149 ). Betulinic acid (BA) inhibits the glycolytic enzymes (HK2/FK1/PEP/PKM2) in CRC cells ( 150 ). Moreover, Atractylenolide I downregulates HK2 expression and blocks the JAK2/STAT3 pathway in CRC cells, inducing cellular regulation and alleviating CRC ( 151 ).…”
Section: Role Of Glycolysis In Colorectal Cancermentioning
confidence: 99%